Islamic Religious Education Teachers' Strategies in Instilling Ethics and Morals to Overcome Bullying Cases at Muhammadiyah Al-Qolam Gemolong Middle School - Febri Bekti Pangestu; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Bullying is a high-intensity behavior perpetrated by one person against another with the aim of hurting or humiliating the victim. This action aims to make the victim feel helpless and suffer. This study aims to explore the strategies of Islamic Religious Education (PAI) teachers in instilling ethical and moral values to prevent and handle cases of verbal bullying at Muhammadiyah Al-Qolam Junior High School. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Based on the results of the study, the most common form of verbal bullying is ridicule or demeaning nicknames, which can cause emotional disturbance to the victim and affect the overall atmosphere of the school. The strategies implemented include religious habituation programs, counseling services, counseling related to bullying, giving advice, and periodic evaluation and supervision. Islamic education is used as the main approach to build good morals, instilling the values of empathy, tolerance and respect for others. However, the obstacles faced include the tendency of students to repeat bullying behavior even though they have been given guidance. Therefore, cooperation between teachers, students, parents and the community is needed to create a positive, conducive, bullying-free school environment that supports good character development.